2002
DOI: 10.1097/00005131-200201000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Admission Hemoglobin Level and Outcome After Hip Fracture

Abstract: Patients at risk for poor outcomes after hip fracture can be identified by assessing hemoglobin levels at hospital admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
140
3
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 37 publications
9
140
3
11
Order By: Relevance
“…13 In elderly patients with hip fracture, anaemia (Hb ,12 g dl 21 for females and ,13 g dl 21 for males) was significantly associated with 2-to 5-and 3-fold increases in the multivariate-adjusted risk of 6 and 12 month mortality, respectively. 14 Patients with Hb ,10 g dl 21 were at a 5-fold increased risk of death. Subsequent studies have confirmed the association between preoperative anaemia and postoperative mortality in this population, 15 16 and in patients undergoing other types of surgery.…”
mentioning
confidence: 99%
“…13 In elderly patients with hip fracture, anaemia (Hb ,12 g dl 21 for females and ,13 g dl 21 for males) was significantly associated with 2-to 5-and 3-fold increases in the multivariate-adjusted risk of 6 and 12 month mortality, respectively. 14 Patients with Hb ,10 g dl 21 were at a 5-fold increased risk of death. Subsequent studies have confirmed the association between preoperative anaemia and postoperative mortality in this population, 15 16 and in patients undergoing other types of surgery.…”
mentioning
confidence: 99%
“…transfusion therapy and increased rates of postoperative infection. [13][14][15] Admission Hb levels have also been shown to impact on postoperative functional recovery in an elderly population with hip fractures 9,16,17 and on quality of life after total hip arthroplasty. 18 Due to the surge of new anticoagulant and antiplatelet drugs these guidelines require frequent updating.…”
Section: S17 Novel Intravenous Iron Therapiesmentioning
confidence: 99%
“…Así pues, si en lugar de comparar el resultado con la capacidad de deambulación tras la fractura, se compara con el nivel previo de los sujetos estudiados las tasas de recuperación son del 20 al 36% a los 3 ó 4 meses (55,65,89), 33 al 75% a los seis meses (47,90), y del 40 al 80% a los 12 meses (34,53,55,56,65,71,73,89,91,92). Por lo general, las series publicadas muestran que el uso de ayudas instrumentales para la deambulación aumenta con respecto a la situación previa a la fractura (58,81,93).…”
Section: Tasa De Recuperaciónunclassified
“…Persiste una limitación en las actividades de la vida diaria incluso a los 9-10 años en más de un tercio de los supervivientes (59,96). Sin embargo, por el contrario, existen estudios que, al comparar con la capacidad de los pacientes para caminar antes de la fractura, encuentran mayores tasas de recuperación del nivel de independencia previo para las actividades básicas (57,65,71,92) e instrumentales (65,71) que para la recuperación de la habilidad para caminar (57,65,71).…”
Section: Tasa De Recuperaciónunclassified